Identifikasi Produk Unggulan Nagari Sikabu untuk Inkubasi Bisnis yang berkelanjutan - Fithri, Prima; Wisnel; Andre, Hanalde; Refdi, Cesar Welya (Jurnal Hilirisasi IPTEKS, 2025)
Nagari Sikabu, located in Padang Pariaman Regency, is an agrarian area with strong potential in corn production as its leading agricultural commodity. However, the utilization of corn has largely been limited to sales in raw form, resulting in relatively low economic value for the local community. This condition indicates a gap between abundant natural resources and the community’s capacity to transform them into value added products. Therefore, this community service program was designed to empower local residents through a sustainable business incubation model for corn based products using a participatory approach. The methods applied included field observations, participatory interviews, Focus Group Discussions (FGDs), and SWOT analysis to map the strengths, weaknesses, opportunities, and threats in developing processed corn products. The results identified that derivative products such as corn chips, corn emping, and corn brownies have strong prospects to become local flagship products. Training sessions and workshops successfully improved community skills by 42%, particularly in food processing techniques, packaging, pricing, and digital marketing. Furthermore, the program facilitated the establishment of a Community Business Group (Kelompok Usaha Bersama/KUB) as an institutional platform for collective business development and local economic strengthening. In conclusion, the corn based business incubation program proved effective in enhancing community capacity, strengthening business institutions, and opening new entrepreneurial opportunities in Nagari Sikabu. For sustainability, continuous assistance is required in product legalization, innovative packaging technology, and integration with digital marketing channels so that processed corn products can penetrate wider markets and contribute to local economic independence.